Developing Graphene Grids for Cryoelectron Microscopy - Fan, Hongcheng; Sun, Fei (Frontiers in Molecular Biosciences, 2022)
Cryogenic electron microscopy (cryo-EM) single particle analysis has become one of the major techniques used to study high-resolution 3D structures of biological macromolecules. Specimens are generally prepared in a thin layer of vitrified ice by using a holey carbon grid. However, the sample quality using this type of grid is not always ideal for high-resolution imaging even when the specimens in the test tube behave ideally. Various problems occur during a vitrification procedure, including poor/nonuniform distribution of particles, preferred orientation of particles, specimen denaturation/degradation, high background from thick ice, beam-induced motion, etc., which have become important bottlenecks in high-resolution structural studies using cryo-EM in many projects. In recent years, grids with support films made of graphene and its derivatives have been developed to efficiently solve these problems. Here, the various advantages of graphene grids over conventional holey carbon film grids, functionalization of graphene support films, production methods of graphene grids and origins of pristine graphene contamination are reviewed and discussed.